PENGARUH PESAN IKLAN, KREATIVITAS IKLAN, KREDIBILITAS CELEBRITY ENDORSER DAN MEDIA KOMUNIKASI TERHADAP EFEKTIVITAS IKLAN DALAM MENUMBUHKAN BRAND AWARENESS PRODUK SAMPO LIFEBUOY - Andiyaksa, Muhammad; Khasanah, Imroatul (Diponegoro Journal of Management, 2017)
An effective ad is an ad that can foster awareness for always remembering to be a brand product.  The  background  to  the  problems  that the consumer  awareness  of  the  ads  delivered shampoo Lifebuoy brand has decreased, look at Top Brand Index, Top of Mind Advertising and TOM Brand that Lifebuoy shampoo decreased significantly when compared with other similar brands of shampoo. This study aims to describe and analyze the effects of advertising messages, advertising creativity, credibility celebrity endorser and communication media on the effectiveness of advertising in aim to growing up brand awareness.The population in this study were students of Diponegoro University in Semarang who have  seen  Lifebuoy  shampoo  ad  impressions  on  television.  By  using  a  sampling  technique, purposive sampling, then obtained a sample of 100 respondents. The analytical tool used in this research is multiple linear regression. Prior to the regression test, first tested the validity and reliability and classic assumption.The results showed that the advertising message shown to have a significant positive influence on the effectiveness of advertising. Advertising creativity has a positive and significant impact on the effectiveness of advertising, meaning that the more creative ads delivered, then make the audience pay attention to these ads in detail and detail so that is expected to cause a rapid impact in efforts to increase the effectiveness of advertising. Credibility of celebrity endorser positive influence on the effectiveness of ads. The results also proved that the communications media  positive  and  significant  impact  on  the  effectiveness  of  advertising.  Effectiveness  of advertising has a positive significant impact to brand awareness, it means that the ad who has a message, creativity, credibility celebrity endorser, and media communication is good and right it will increase the effectiveness of your ad which will grow brand awareness